Cover Image, Volume 138, Issue 13. Issue 13 (22nd December 2020) - Yang, Qianyu; Gao, Chen; Zhang, Xuemei; Zhao, Xingyu; Fu, Yiqing; Tsou, Chihui; Zeng, Chunyan; Yuan, Li; Pu, Zejun; Xia, Yiqing; Sheng, Yuping; Fang, Yu
Abstract : A hydrophobic association hydrogel poly(acrylamide‐acrylic acid‐stearyl methacrylate) [P(AAm‐AAc‐SMA)] was designed and fabricated by Chen Gao and colleagues. After the hydrogel was dehydrated under vacuum, the morphology of the gel was characterized by scanning electron microscope (SEM). As shown in the image, disc‐like (50‐120 μm in diameter) and rod‐like (60‐80 μm in length) morphologies have been observed, as well as a few fantastic crater morphologies, which may be ascribed to the aggregation of the hydrophobic SMA segments during the dehydration of the gel. DOI: 10.1002/app.50308